COVID-19 mRNA booster vaccination induces robust antibody responses but few adverse events among SARS-CoV-2 naïve nursing home residents - Itamochi, Masae; Yazawa, Shunsuke; Saga, Yumiko; Shimada, Takahisa; Tamura, Kosuke; Maenishi, Emi; Isobe, Junko; Sasajima, Hitoshi; Kawashiri, Chikako; Tani, Hideki; Oishi, Kazunori (Scientific reports, 2024)
Residents in nursing homes face heightened COVID-19 risks. We aimed to assess the adverse events (AEs) rates and antibody responses after the first to the fifth dose of COVID-19 mRNA vaccination in a nursing home cohort. Ninety-five SARS-CoV-2 naïve participants consisted of 26 staff (median age, 51 years) and 69 residents (median age, 88 years). Life-threatening AEs were reported in neither residents nor staff. The severity of non-life-threatening AEs was graded, and severe AEs were reported only in staff. The AEs rates were considerably lower in residents, compared to those in staff. Anti-RBD IgG and the neutralizing titers (NTs) against Wuhan and Omicron BA.4/BA.5 did not differ significantly between those with ‘any AE’ and ‘no AE’ among both staff and residents two months after the second, third and fifth doses, while the anti-RBD IgG significantly differed between two groups after third dose in residents. These findings suggest that the anti-RBD IgG and the NTs increase regardless of the occurrence of AEs. Our study underscores a robust antibody response in both in staff and residents, and fewer AEs following COVID-19 vaccination in SARS-CoV-2 naïve residents than staff, supporting the recommendation for mRNA booster doses in older adults at high-risk care facilities.